The Future of Nature Conservation in Amazonia: Evidence From Transboundary Protected Areas - Cardona, Walter Cano; de Jong, Wil; Pokorny, Benno (Frontiers in Forests and Global Change, 2022)
Biological diversity has been recognized as a global asset that is key to the well-being and survival of present and future generations. In response to massive destruction of the world’s ecosystems, the international community has agreed on several initiatives, most importantly, the Convention on Biological Diversity (CBD) in 1992, which is the basis of the Strategic Plan for Biodiversity 2011–2020, and the 20 Aichi Biodiversity Targets. A central instrument of these initiative are protected areas. The nine Amazonian countries alone, have designated 390 million hectares of protected forest areas, some of which are under very heavy pressure. As explicitly stated in Aichi Targets 11, 17, and 18, the effective governance and management of these protected areas requires the active participation of indigenous and other local resource user groups and respect for their traditional knowledge and customary practices. This manuscript analyzes to what extent and in which way these targets have been achieved by analyzing three transboundary protected areas in Brazil, Peru, and Bolivia constituted of five national parks. The analysis shows that important progress has been made in terms of the local participation and the generation and sharing of economic benefits, mostly due to the engagement of non-governmental organization (NGOs) funded from overseas development assistance (ODA) sources. However, many of the established mechanisms show major shortcomings, such as power imbalances, lack of legitimacy of decision-makers, unclear responsibilities, unresolved logistical challenges, and the lack of financial support. In addition, the functionality of local governance structures is severely threatened by the vagaries of national policies that often put biodiversity conservation and economic development at loggerheads. In order to ensure the functionality of protected areas in the Amazon region, binding and sufficient commitments by national governments are needed for genuine and effective local governance.